Feasibility of Fortification of Pine-apple, Orange and Paw-paw Juice Blends with Food Grade Plant ash - Okwunodulu, Innocent; Oriala, Moudlyn; Ndife, Joel; Nwachukwu, Ann (Indonesian Food Science and Technology Journal, 2022)
Feasibility of plant ash fortification on the proximate, mineral, Physico-chemical and sensory properties of juice blends from paw-paw, orange and pineapple fruits was investigated with standard analytical methods. The juice blend was divided into 5 parts of 500 ml each and four portions were fortified with 5%, 10%, 20%, and 30% of plant ash while the remaining unfortified portion was the control. With increase in plant ash fortification levels, proximate composition revealed increase in ash (0.8 to 2.50%) and carbohydrate (5.60 to 5.95%) while protein (1.45 to 1.05%), fat (2.00 to 1.15%) and moisture (90.15 to 88.40%) decreased. Sodium (25.39 to 57.12 mg/100ml), potassium (80.53 to 104.78 mg/100ml), magnesium (51.60 to 80.64 mg/100ml) calcium (102.62 to 141.79 mg/100ml) and phosphorous (53.54 to 79.89 mg/100ml) all increased. The pH (4.85 to 9.10) and total soluble solids (7.05 to 10.95) increased while colour (0.138 to 0.110) decreased. General acceptability (7.10 to 6.20) decreased. Fortification with plant ash is feasible but should not exceed 10% to avoid rejection.